EARLY DIAGNOSIS OF ACUTE KIDNEY INJURY BY URINARY NEUTROPHIL GELATINASE ASSOCIATED LIPOCALIN IN ADULT CRITICALLY ILL PATIENTS - Shoaib, Muhammad; Mahmud, Syed Nayer; Safdar, Muhammad (Journal of Ayub Medical College Abbottabad, 2018)
Background: Acute kidney injury (AKI) is a major cause of mortality and morbidity in the hospitalized patients. It is also a risk factor for chronic kidney disease and advance renal failure. Early diagnosis with new biomarkers for AKI can prevent and/or reverse the process before rise in serum creatinine and symptomatic renal failure. This study is aimed at the accuracy of Urine neutrophil gelatinase associated lipocalin (NGAL) for detection of AKI at an early stage. Methods: It is a descriptive, cross sectional study conducted in the Medical Intensive Care Unit of Shifa International Hospital, Islamabad. Total 97 patients admitted in intensive care unit, age from 18 to 75 years, fulfilling the inclusion criteria were included by non-probability, consecutive sampling technique. Duration of study was six months, from 1st February 2014 till 31st July 2014. Urine samples of study population were tested for NGAL and simultaneously serum creatinine levels were checked, which were repeated at 48 hours for diagnosis of AKI. Patients with AKI and positive values of NGAL were considered true positive while patients without AKI and negative values of NGAL were considered true negative. Accuracy of NGAL was then calculated and effect modifiers like age and gender checked by chi square testing. Results: Mean age of the participants was 57.76 years with the range of 26 to 74 years. Out of the total population of 97 patients, 48.5% were males and remainder 51.5% were females. The study found that the accuracy of the urinary NGAL in diagnosis of AKI when compared with serum creatinine was 90.7%. Conclusion: Urine NGAL is an accurate marker of AKI in critically ill patients. Therefore, it should be included in the diagnostic workup of AKI in early stages. Keywords: Urine neutrophil gelatinase associated lipocalin (Urine NGAL); Acute kidney injury; Serum creatinine; critically ill patients